Contamination of selected recreational areas in Lublin Province, Eastern Poland, by eggs of Toxocara spp., Ancylostoma spp. and Trichuris spp. - Hubert Bojar; Teresa Kłapeć (Annals of Agricultural and Environmental Medicine, 2018)
Introduction While using recreational areas, people take with them accompanying animals (dogs, cats). These animals are the main source and reservoir of dangerous zoonoses, including parasitoses caused by genera of nematodes, also called roundworms, Toxocara spp., Trichuris spp. and Ancylostoma spp. Attention should also be paid to the possibility of contamination of recreational areas with the eggs of intestinal parasites by wild animals (e.g. red fox).